Analysis of BI7DRR’s Relationship to Inflation 2018-2023: Case Study on Granger Causality - Sukirman, M. Wesla Dhifayana; Bachtiar, Arief (PT. Riset Press International, 2024)
An assessment of a nation's economic health may be made by examining its rate of inflation. Good economic conditions can be said if the inflation rate is low or at the predetermined inflation target position. A new reference rate called BI7DRR is transactional, meaning it is exchanged on the market, and it promotes the depth of the financial markets. It also has a higher correlation with money market interest rates. The aim of this research is to find a reciprocal relationship (causality) between BI7DRR and inflation and to analyze the characteristics used in determining interest rates. This study employed a quantitative approach using techniques from descriptive analysis. The data used in this research is BI7DRR historical data for 2018-2023 and historical inflation data for 2018-2023. The data was tested using the Granger Causality test with the help of Eviews 12 software. The results of the Granger Causality Test showed an Inflation Probability value of 0.0457 0.05 (5%) and a BI7DRR Probability value of 0.2788 0.05 (5%). So it can be said that the Inflation variable has a relationship with the BI7DRR variable and the BI7DRR variable has no relationship with the Inflation variable. According to the research description given above, the following conclusions can be drawn: there is a one-way relationship between the inflation and BI7DRR variables in 2018–2023, the BI7DRR variable and the inflation variable in 2018–2023, and based on the findings of the Granger causality test and supporting references, it can be claimed that historical inflation data is used to determine the reference interest rate in the form of BI7DRR. This means it is backward-looking